VINCRISTINE AFFECTS THE REDOX REACTIVITY OF HEMOGLOBIN - CÎRJEU, Victoria; PUȘCAȘ, Cristina; SILAGHI-DUMITRESCU, Radu (Studia Universitatis Babeș-Bolyai Chemia, 2021)
The anticancer drug vincristine, known to act by inhibiting tubulin function in human cells, is shown to affect autoxidation rates in hemoglobin – either alone or under conditions where nitrite acts as an initiator in a nitrosative stress cascade. This behavior mirrors those observed by us with four other antitubulin agents - irinotecan, docetaxel, paclitaxel and vinorelbine.